The use of using ladybugs to control the abundance of the chestnut moth - Bashchenko, M. (Quarantine and plant protection, 2024)
Goal. The aim of the work was to evaluate the possibilities of using the eggs of the chestnut moth to feed coccinellids in laboratory conditions. Methods. Research was conducted in the laboratory of pesticide application technology. In laboratory conditions, experiments were conducted according to the following scheme: 5 pairs of coccinellid adults (Adalia bipunctata L.) were placed in each garden, in which corrugated filter paper was previously placed. After that, the garden was tightly closed with a cloth moistened with water with added sugar. Subsequently, one-day-old eggs of the chestnut moth were placed in the garden with coccinellids and the investigated insects were kept at a temperature of 25°C and a relative humidity of 50—60%. Coccinellids, which fed on the cereal aphid Schizaphis graminum Rond (previously propagated on wheat seedlings), were taken as a control. The repetition of the experiment is 5 times. Accounting was carried out daily. The obtained results were processed statistically, according to standard methods of processing the results of biological experiments. Results. The results showed that coccinellids that fed on day-old chestnut moth eggs laid no more than 75.0 eggs, while the fecundity of control individuals reached 363.0 specimens. The resulting coccinelid eggs were planted in separate gardens for further research. The development of entomophagous eggs was 5—8 days. The reborn larvae continued to be fed with chestnut moth eggs in the experimental variants, and with grain aphids in the control variants. The duration of development of the first larval instar was 2—3 days, but they did not survive to the third instar in the experimental variants. Only the control individuals completed the full cycle of their development. At the same time, the larval stage lasted 9—14 days, the pupa — 4—6 days. The entire cycle of development is 15—24 days. After 8—10 days after the emergence of coccinellid adults, they mate. Conclusions. It has been proven that the eggs of the chestnut moth are not a complete food source for coccinellids of the species A. bipunctata L., causing a significant suppression of the fertility of this predator and the death of its larvae up to the third age.